Design and Implementation of Single Axis Solar Tracking System: Utilizing GPS, Astronomical Equations, and Satellite Dish Actuator for Optimal Efficiency - Rizgar Ahmed Salih; Karzan Qadir Mohammed; Peshawa Osman Hama; Rawaz Othman Hassan; Barham Kamal Noori (Journal of Engineering)
Globally, the focus is on maximizing the energy yield and efficiency of PV systems as an essential renewable energy source. Different methods have been proposed to achieve this goal. Where the sun’s location in the sky is changed during the day, a tracking mechanism has been proposed as a promising technology to harness the maximum amount of solar radiation by PV system as compared to the fixed panels. In this study, the design and implementation of a polar single-axis tracking system is presented to improve the energy efficiency of PV system through angular variation during the day using the proposed tracking system. This is achieved by interconnecting some devices that include GPS sensors and satellite dish actuators as the main components that are managed and controlled using astronomical equations. The designed system is tracked in a discrete manner that can be adjusted automatically during the day related to each degree change of azimuth angle of the sun from sunrise to sunset. The system has been field tested in Sulaymaniyah, Iraq, to evaluate its performance in different weather conditions and compare it with a fixed PV system. The test results for the clear sky indicated that the increased amount of energy production for the tracking system is 36.6% as compared with the stationary panel. Whereas, for a mostly cloudy day the measured amount of increase was 18.5%. This improvement of the harnessed energy for PV systems is important to make the system more efficient and sustainable.